Pengaruh Model Pembelajaran Advance Organizer Terhadap Minat dan Hasil Belajar Peserta Didik Kelas XI pada Mata Pelajaran Ekonomi di SMA Negeri 13 Pangkep - Hendra, Hendra; Fahreza W, Muhammad; Devilla, Rego (CV. Rayyan Dwi Bharata, 2025)
This study is a quasi-experimental research with a nonequivalent control group design. This design was chosen because the students who are the subjects of the study could not be randomly assigned to either the control or experimental group. The objectives of this study are: (1) To determine the effect of the Advance Organizer learning model on students' interest in learning Economics in class XI at SMA Negeri 13 Pangkep Boarding School; (2) To determine the effect of the Advance Organizer learning model on students' learning outcomes in Economics in class XI at SMA Negeri 13 Pangkep Boarding School; and (3) To determine the effect of the Advance Organizer learning model on both students' interest and learning outcomes in Economics in class XI at SMA Negeri 13 Pangkep Boarding School. In this study, data was collected through questionnaires, documentation, and observations, with instruments including surveys and documentation. The population of this study consists of the students in the Economics specialization class at SMA Negeri 13 Pangkep. The results of the study indicate the following findings: (1). The test results partially show that the use of the Advance Organizer learning model positively affects students' interest in learning Economics in the class XI Economics specialization at SMA Negeri 13 Pangkep, with better learning outcomes in the experimental group compared to the control group. (2). The test results also partially show that the use of the Advance Organizer learning model positively affects students' learning outcomes in Economics in class XI at SMA Negeri 13 Pangkep, with higher interest in learning Economics in the experimental group compared to the control group. (3). Simultaneously, the test results indicate that the use of the Advance Organizer learning model positively affects students' learning outcomes, where both interest and learning outcomes in Economics are better in the experimental group than in the control group.